Revision of the Afrotropical Lycorininae (Ichneumonidae; Hymenoptera) with description of a new species from South Africa - Rousse, Pascal; Noort, Simon Van (Zootaxa, 2013)
We revise the Afrotropical Lycorininae and describe Lycorina yui Rousse & van Noort sp. nov. from South Africa. An illustrated key to Lycorininae species of the Afrotropical region is provided. Lycorina continentalis (Benoit, 1953) is con-sidered a junior synonym of Lycorina fici Seyrig, 1932, and is newly reported from Uganda and South Africa. Online di-chotomous and interactive Lucid keys are available at http://www.waspweb.org.